Analisis Node dengan Metode Degree Centrality dan Sentiment Analysis dalam Acara G20 Indonesia di Twitter - Harnanda, Elifas Gavra; Mailoa, Evangs (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Twitter is a popular social media platform that is used to communicate through exchanging messages and one of them can use hashtag #G20Indonesia. #G20Indonesia is a hashtag originating from the G20 Indonesia event which was held in Bali from 15 to 16 November 2022. It aims to analyze data on research containing "#G20Indonesia". This analysis uses social network analysis and sentiment analysis methods. Analysis of social networks to find the most influential account in the network that is formed, analysis of social networks can use the degree of centrality in the maintenance of the most influential account. Sentiment Analysis to categorize Twitter tweets using AWS Comprehend with 10,001 nodes and 6,839 edges of data taken. The results of research conducted based on the method used are the account @wishnutama which is an influential account based on the communication network formed with #G20Indonesia on Twitter and the sentiment formed is 63.8% for neutral sentiment, 35.4% for positive sentiment and 0.8% for negative sentiment.